MORFOGENESIS DAN INDUKSI KALUS TIN (Ficus carica L.) PADA MEDIA MURASHIGE DAN SKOOG (MS) DENGAN PENAMBAHAN BENZYLAMINOPURINE - Pangesti Nugrahani; Didik Utomo Pribadi (JURNAL AGROTEKNOLOGI, 2019)
Fig is one of the introduced fruit trees, which became popular in Indonesia. Its leave and fruit can be used as medicine and healthy food. The effect of different combination concentration of BAP (Benzylaminopurine) and 2,4-D (2,4-dicholophenoxy acetic acid) on callus induction from leaf segment of Ficus carica L. were studied. The effect of differrent combination of BAP and coconut water on morphogenesis of single node of Fig was also investigated. The study was arranged as factorial design in completely randomized design in two experiments with 5 repetitions for each treatment. The factors of experiment I were the concentration of BAP (0,1, and 2 mg/L) and the concentration of 2,4-D (0,1, and 2 mg/L). And the factors of experiment II were the concentration of BAP (1 and 2 mg/L) and the concentration of coconut water (100 and 150 mL/L). Each treatment consisted of 10 replicates (bottles). The result showed that MS (Murashige and Skoog) medium supplement with 100 mL/L coconut water, enhanced shoot development. MS medium supplemented with 2,4-D 2 mg/L, enhanced callus induction of Ficus carica L. Keywords: 2,4-D, morphogenesis, BAP, callus, Ficus carica L.